Nano-scale modulus mapping of biological composite materials: Theory and practice. (June 2017) - Zlotnikov, Igor; Zolotoyabko, Emil; Fratzl, Peter
Abstract: The mechanical behavior of materials depends to a large extent on their properties at the nanoscale and, therefore, novel characterization techniques with sub-micron spatial resolution were developed in the last decades. Among them are the variety of tools for probing local elastic and viscoelastic properties of materials, the methods such as nanoindentation and AFM- and nanoindenter-based measurements using force modulation. In this review, we describe the nanoindenter-based nanoscale modulus mapping technique, which emerged as an extremely powerful tool for providing quantitative information on the storage and loss moduli distributions in complex nanocomposites. Since the tip penetrates only a few nanometers into the materials, this technique provides a superior lateral resolution in the order of 20 nm. All aspects of the method are covered, including a historical perspective, theoretical analysis, instrumentation, and examples of its application for studying multiphase structures and interfaces. The main focus of this review is the challenging field of natural bio-composites, which consist of stiff and compliant components, often with nanometric dimensions. Gradients of mechanical properties across the nm-sized features in biological materials are of upmost importance for their mechanical performance. Quantitative information on the nano-scale moduli distributions in these structures can hardly be achieved by other means.